PAK1‐cofilin phosphorylation mediates human lung adenocarcinoma cells migration induced by apelin‐13. (May 2016) - Lv, Deguan; Li, Lanfang; Lu, Qixuan; Li, Yao; Xie, Feng; Li, Hening; Cao, Jiangang; Liu, Meiqing; Wu, Di; He, Lu; Chen, Linxi
Summary: Adipocytokines apelin peptide, the ligand of APJ (putative receptor related to the angiotensin receptor AT1 ), plays key roles in the pathogenesis and deterioration of cancer. In lung cancer, apelin elevating microvessel densities has been reported. Our previous research has characterized that apelin‐13 promoted lung adenocarcinoma cell proliferation. However, the effect of apelin on metastasis in lung adenocarcinoma and the underlying mechanisms remain unclear. This study shows that apelin‐13 induced human adenocarcinoma cell migration via the APJ receptor. Apelin‐13 phosphorylated PAK1 and cofilin increase the migration of lung adenocarcinoma cells. Moreover, the results verify that over‐exprssion of apelin and APJ contributed to reducing the effect of doxorubicin and razoxane on inhibiting lung adenocarcinoma cells metastasis. Hypoxia activated APJ expression and apelin release in lung adenocarcinoma cells. The results demonstrate a PAK1‐cofilin phosphorylation mechanism to mediate lung adenocarcinoma cells migration promoted by apelin‐13. This discovery further suggests that APJ and its downstream signalling is a potential target for anti‐metastatic therapies in lung adenocarcinoma patients.